RELEVANSI ETIKA KEADILAN DENGAN PENGAMBILAN KEPUTUSAN GURU DALAM DUNIA PENDIDIKAN : STUDI KASUS DI MTSN X MERANGIN - Riska Meisyi Putri; Hidayatul Fadliah; Andri Ani Suryawijaya; Renny Yuliarti; Dismawati; Yusrizal; Retno Wahyu Ningsih (STKIP Subang, 2026)
This study aims to describe the relevance of the ethics of justice to teacher decision-making in education, specifically at MTsN X Merangin. The ethics of justice emphasizes equal treatment, moral responsibility, and respect for student rights. This study used a descriptive qualitative approach with three teachers and one principal as subjects. Data were obtained through interviews, observation, and documentation, then analyzed thematically. The results indicate that teachers at MTsN X Merangin have attempted to apply the principle of justice in decision-making related to learning, assessment, and student development. This implementation is evident in providing equal opportunities for students to express their opinions, process-oriented assessments, and resolving violations using a dialogical approach. However, a dilemma remains between normative justice (based on rules) and contextual justice (based on empathy and individual situations). Overall, the ethics of justice has been shown to have strong relevance to the formation of wise, humane, and morally value-oriented teacher decisions in education.